Finite Element Simulation Study on 2A14 Aluminum Alloy Conical Cylinder Parts Based on Simufact - Gao, Yanan; Li, Jiawei (International Journal of Mechanical and Electrical Engineering, 2025)
The hot rolling process of a conical cylindrical part made of 2A14 aluminum alloy was investigated using finite element simulation with Simufact-Forming. A numerical rolling model was established, and the forming behavior of the component at different deformation stages was systematically analyzed. The simulation results indicate that the proposed approach effectively reflects the deformation characteristics of conical cylinders and provides practical guidance for the rolling of non-standard ring components. This study demonstrates that finite element simulation not only contributes to improving the forming quality of ring parts and reducing production and development costs but also enhances industrial competitiveness. Furthermore, the findings offer valuable insights for the practical application of radial–axial rolling in complex ring components.